CORMAC MCCARTHY’S “THE ROAD” AS A WAY OUT (Conferencea, 2024)
Literature and art have always been reflections of the reality of each era. By analysing them we can become acquainted with the socio-political circumstances of the time, or even explore the concerns and fears of the population. Cormac McCarthy’s last novel The Road portrays a post-apocalyptic world where all flora and fauna have been blown to smithereens, and the few remaining survivors follow a road longing for a better future. The American author describes an uninhabitable grey world with clear dystopian features, building a novel that could be considered to be a critique towards the current environmental issue, and even as a warning. Overall, I will focus on the role of place and nature in a post-apocalyptic society, analysing their interaction with human relationships and moral values. In order to understand all the factors that influence the survival of the main characters in the novel, I will follow three different methodologies. Firstly, I will analyse the novel as a dystopian story through Utopian Studies, highlighting McCarthy’s use of place to create a dystopian atmosphere. Thus, I will make use of an ecocritical approach in order to analyse the absence of nature and its consequences in human behaviour. Thirdly, focusing on a more social aspect, I will examine the cultural symbolism of such elements as the road or the myth of the American West, and the contrast between the human values of the two main characters. In summary, through this paper I will conduct an analysis on how McCarthy reflects current socio-political and environmental concerns through a touching story in which a devastated landscape leads to a behavioural shift, emphasising the role of nature and place.